Antioxidant and antibacterial activity of extract from two species of mosses: Leucobryum aduncum and Campylopus schmidii - Maria Masitho Makajanma; Intan Taufik; Ahmad Faizal (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Makajanma MM, Taufik I, Faizal A. 2020. Antioxidant and antibacterial activity of extract from two species of mosses: Leucobryum aduncum and Campylopus schmidii. Biodiversitas 21: 1751-1758.  Plants produce a plethora of natural compounds of medicinal value. Although most plant-derived drugs have been identified in angiosperms, some species of mosses from the genera Leucobryum and Campylopus also exhibit antioxidant and antibacterial activity. The research aimed to evaluate the antioxidant and antibacterial activities of two species of these genera, Leucobryum aduncum and Campylopus schmidii, that are common in Taman Wisata Alam Gunung Tangkuban Perahu, West Java. Plants were collected, dried, and extracted in n-hexane or methanol. Antioxidant activity was evaluated by determining the concentration of extract that resulted in 50% reduction of 1,1-diphenyl-2-picrylhydrazine (DPPH) in the DPPH assay. These concentrations were >2000 mg/L for L. aduncum extracts and 1329.02 ± 7.8 mg/L for C. schmidii extracts; these large values are consistent with little antioxidant activity. Antibacterial activity was quantified as the ability of the extracts to inhibit the growth of the Gram-negative and Gram-positive bacteria Escherichia coli and Staphylococcus aureus, respectively. Nonpolar extracts of L. aduncum inhibited the growth of E. coli >50% at a concentration of 32 mg extract/L. Based on combined gas chromatography-mass spectrometry, the antibacterial activity in the non-polar extracts of L. aduncum was attributed to the lipophilic compounds 1-nonadecene, 5-eicosene, and cyclotetracosane. Thus, L. aduncum is a promising candidate as a source of new antibiotics.